Evernimicin (SCH27899) Inhibits a Novel Ribosome Target Site: Analysis of 23S Ribosomal DNA Mutants - Adrian, Peter V. (American Society for Microbiology, 2000)
Spontaneous mutants of susceptible clinical and laboratory isolates of Streptococcus pneumoniae exhibiting reduced susceptibility to evernimicin (SCH27899; MIC, 0.5 to 4.0 mg/liter) were selected on plates containing evernimicin. Four isolates that did not harbor mutations in rplP (which encodes ribosomal protein L16) were further analyzed. Whole chromosomal DNA or PCR products of the 23S ribosomal DNA (rDNA) operons from these mutants could be used to transform the susceptible S. pneumoniae strain R6 to resistance at frequencies of 10(−5) and 10(−4), respectively, rates 10- to 100-fold lower than that for a single-allele chromosomal marker. The transformants appeared slowly (48 to 72 h) on selective medium, and primary transformants passaged on nonselective medium produced single colonies that displayed heterogeneous susceptibilities to evernimicin. A single passage on selective medium of colonies derived from a single primary transformant homogenized the resistance phenotype. Sequence analysis of the 23S rDNA and rRNA from the resistant mutants revealed single, unique mutations in each isolate at the equivalent Escherichia coli positions 2469 (A → C), 2480 (C → T), 2535 (G → A), and 2536 (G → C). The mutations map within two different stems of the peptidyltransferase region of domain V. Because multiple copies of rDNA are present in the chromosome, gene conversion between mutant and wild-type 23S rDNA alleles may be necessary for stable resistance. Additionally, none of the characterized mutants showed cross-resistance to any of a spectrum of protein synthesis inhibitors, suggesting that the target site of evernimicin may be unique.